Bone mineral density in young adults with Prader‐Willi syndrome: A randomized, placebo‐controlled, crossover GH trial - Donze, Stephany H.; Kuppens, Renske J.; Bakker, Nienke E.; van Alfen‐van der Velden, Janiëlle A.E.M.; Hokken‐Koelega, Anita C.S. (Clinical endocrinology (Oxford), 2018)
Summary Context The prevalence of osteoporosis is increased in adults with Prader‐Willi syndrome (PWS). In children with PWS, growth hormone (GH) treatment has beneficial effects on bone mineral density (BMD). BMD might deteriorate after cessation of GH at adult height (AH), while continuing GH might maintain BMD. Objective To investigate the effects of GH vs placebo, and furthermore the effects of sex steroid replacement therapy (SSRT), on BMD in GH‐treated young adults with PWS who had attained AH. Design Two‐year, randomized, double‐blind, placebo‐controlled, crossover GH study. Patients Twenty‐seven young adults with PWS were stratified for gender and BMI and then randomly and blindly assigned to receive GH (0.67 mg/m2/day) or placebo for 1 year, after which they crossed over to the alternative treatment for another year. Measurements Bone mineral density of the total body (BMDTB) and lumbar spine (BMDLS) SDS were measured by dual‐energy x‐ray absorptiometry. Results At AH, BMDTBSDS was significantly lower compared to healthy peers (P < .01), while BMADLSSDS was similar. Both BMDTBSDS and BMADLSSDS were similar during 1 year of GH vs 1 year of placebo. In hypogonadal young adults without SSRT, BMDTBSDS and BMADLSSDS decreased during the 2‐year study (P = .11 and P = .01), regardless of GH or placebo, while BMDTBSDS increased in those with SSRT (P < .01). Conclusions Compared to GH treatment, 1 year of placebo after attainment of AH does not deteriorate BMD SDS in young adults with PWS. In addition, our data suggest that GH is not able to prevent the decline in BMD SDS in hypogonadal young adults with PWS, unless it is combined with SSRT.